Protective effects of selenized yeast on the combination of cadmium-, lead-, mercury-, and chromium-induced toxicity in laying hens - Wu, Caimei; Song, Jingping; Li, Lang; Jiang, Yuxuan; Applegate, Todd J.; Wu, Bing; Liu, Guangmang; Wang, Jianping; Lin, Yan; Zhang, Keying; Li, Hua; Wu, Fali; et al. (Frontiers in Veterinary Science, 2022)
The objective of this study was to investigate the toxic effects of a combination of cadmium (Cd), lead (Pb), mercury (Hg), and chromium (Cr) on laying performance, egg quality, serum biochemical parameters, and oxidative stress of laying hens, as well as the alleviating action of dietary supplementation of selenized yeast. A total of 160 Lohmann pink-shell laying hens (63-week-old) were randomly divided into 4 treatments with 10 replicates of 4 hens each. The treatments were the corn-soybean meal basal diet (control; CON), the CON diet supplemented with 0.4 mg selenium (Se) /kg from selenized yeast (Se); combined heavy metals group: the basal diet added with 5 mg Cd/kg, 50 mg Pb/kg, 3 mg Hg/kg, and 5 mg Cr/kg (HEM), and the HEM diet supplemented with 0.4 mg Se /kg from selenized yeast (HEM+Se). The experimental period lasted for 12 weeks. The HEM diet decreased hen-day egg production, Feed conversion ratio （FCR）, and egg white quality (P < 0.05), but increased (P < 0.05) glutamic oxalacetic transaminase (AST) activity in the serum. HEM induced higher malondialdehyde (MDA) and reactive oxygen species (ROS) in the serum, liver and ovary, and significantly decreased (P < 0.05) the activity of total superoxide dismutase (SOD) and tended to decrease glutathione S-transferase (GST) (P = 0.09) in the serum. Meanwhile, HEM significantly decreased (P < 0.05) activity of SOD, GST, glutathione peroxidase (GPX) and glutathione (GSH) in the liver, and the activity of GPX and GSH in the ovary. Se addition of 0.4 mg/kg significantly (P < 0.05) improved hen-day egg production, FCR, and increased AST concentration, and some enzyme activity, in the serum, liver and ovary. In conclusion, dietary HEM exposure depressed laying performance and egg white quality was likely due to an impaired antioxidant capacity, disrupted hepatic function, and elevated HEM accumulation in the egg yolk and egg white of laying hens. Se addition of 0.4 mg/kg ameliorated toxic effects of HEM on laying performance, oxidative stress, and hepatic function.